Mechanical, Thermal, and Ablative Properties of Silica, Zirconia, and Titania Modified Carbon-Phenol Ablative Composites - Raghu Raja P. Kuppusamy; Swati Neogi; Santoshi Mohanta; Moganapriya Chinnasamy; Rajasekar Rathanasamy; Md. Elias Uddin (Advances in Materials Science and Engineering)
The effect of nanozirconia, nanotitania, and fumed silica on the mechanical, thermal, and ablation behaviour of carbon-phenolic (C-Ph) composites is investigated. The inorganic nanofillers at different loading percentage are used to prepare nano-C-Ph panels by the compression moulding technique. The dispersion of nanofillers is confirmed through SEM analysis. After manufacturing of C-Ph laminates, the mechanical properties such as tensile strength and hardness are evaluated and the effect of these fillers is investigated. Thermal conductivity, thermal erosion, and back wall temperatures were measured to understand the thermal and ablation behaviour of nano-C-Ph laminates. Additionally, the ablation mechanism is analysed by performing SEM analysis of partially and fully burnt composite laminates. The erosion resistance and burnout time of zirconia-C-Ph panels significantly improved with increase in filler loading percentage; however, the back wall temperature rises with filler loading. Titania-filled C-Ph panels show a better control over the back wall temperature but with a poor erosion control. Silica-filled composite panels have shown a balance between decreased back wall temperature with a reasonable erosion rate and burnout time.